CORPORATE SOCIAL RESPONSIBILITY, GROWTH, DAN KINERJAKEUANGANSEBAGAI VARIABEL MODERATING - OKTAVIANA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract : The purpose of this research is to test the effect of CSR disclosure on financial performance of companies with growth as a moderating variable. This research includes growth as a moderating variable because firms with growth should have higher and more knowledgeable social responsibility. This research used Corporate Social Disclosure Index (CSDI) as a measure of CSR disclosure, based on indicators from Global Reporting Initiatives (GRI). The samples of this research are 9 firms of agriculture sector listed in Indonesian Stock Exchange (IDX) in 2009 until 2012. The results of this research indicate that the disclosure of CSR does not has effect on Return on Asset (ROA) and Return on Equity (ROE) as a measure of corporate financial performance. Growth as moderating variables also can not affectthe relationship between CSR disclosure and corporate financial performance. Keywords: CSR, ROA, ROE, and growth.